2022
DOI: 10.21203/rs.3.rs-2205821/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of acetazolamide - the ionic surfactant on the double layer parameters at the R-AgLAFe/ chlorates(VII) interface

Abstract: Adsorption of acetazolamide (ACT) and the mixed adsorption layers of acetazolamide (ACT) - sodium 1-decanesulfonate (SDS) and acetazolamide - hexadecyltrimethylammonium bromide (CTAB) formed at the R-AgLAFe/ chlorates(VII) interface is described. The systems were characterized by the measurements of differential capacity, potential of zero charge, and surface tension at this potential. The adsorption parameters determined in the studied systems indicate the SDS domination in the adsorption equilibria formation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…As shown earlier, ACT is adsorbed on the electrode [ 24 ] and can shift the equilibrium complexation of In(III) ions favorably. It should also be noted that acetazolamide has complex-forming properties, most likely due to its structure containing free electron pairs at the sulfur and nitrogen atoms ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As shown earlier, ACT is adsorbed on the electrode [ 24 ] and can shift the equilibrium complexation of In(III) ions favorably. It should also be noted that acetazolamide has complex-forming properties, most likely due to its structure containing free electron pairs at the sulfur and nitrogen atoms ( Scheme 1 ).…”
Section: Resultsmentioning
confidence: 97%
“…It is also important to note the different character of the dependence ( Figure 7 ) above ACT concentration of 1 × 10 −4 mol·dm −3 , which may suggest changes in the electrode mechanism [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that adsorption does not limit the surface area of the electrode but activates it further. [25] Furthermore, the orientation of the adsorbed ACT molecules on the surface of a cyclically renewable liquid silver amalgam film electrode (R-AgLAFE), due to the change in water activity in basic electrolyte solutions, plays a significant role in the formation of active In-ACT complexes, which are the substrate in the electroreduction process. Since electron is transferred to the antibonding molecular orbital of the In(III) complex reactants, the inner sphere reorganisation can be noticeable.…”
Section: Discussionmentioning
confidence: 99%
“…[19] The competitive adsorption of acetazolamide, water and to a small extent, ClO 4 À in the double layer interface should be considered. [25] The presence of active In-ACT complexes in the electrode mechanism in the electrolyte solutions with much lower water activity is not excluded either. [10] All these phenomena probably translate into a change in the electrode mechanism in more concentrated chlorates(VII) solutions, which also involves changes in the dynamics of the catalytic activity of ACT.…”
Section: Clo4mentioning
confidence: 99%